2013
DOI: 10.1111/dsu.12254
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Complication Rates of Full-Thickness Skin Graft Repair of Lower Extremity Wounds After Mohs Micrographic Surgery

Abstract: FTSG is a consistent and safe reconstructive option for the management of lower extremity wounds after MMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
0
14
1
1
Order By: Relevance
“…Primary and delayed closure, as well as grafting of a wound are well documented options and should be attempted in both the simple wound, those where expedited recovery is required, or where more complex reconstructive failure would be disastrous [ 8 ].…”
Section: Reconstruction Options: the Reconstructionmentioning
confidence: 99%
“…Primary and delayed closure, as well as grafting of a wound are well documented options and should be attempted in both the simple wound, those where expedited recovery is required, or where more complex reconstructive failure would be disastrous [ 8 ].…”
Section: Reconstruction Options: the Reconstructionmentioning
confidence: 99%
“…Flap and graft reconstruction are the types of surgeries associated with the highest risk for SSI . Graft take in lower leg surgeries have been reported at rates of 64% to 90%, depending on the study . The risk of bleeding complications has previously been reported to be between 0.3% and 3% and for necrosis between 1.7% and 8.6% …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the risk for postoperative complications within dermatological surgery has been between 0.7% and 29%, with some studies separately focusing on, for example, below the knee, dermatology inpatients, or FTSGs, all factors significantly influencing complication risk. 1,6,[13][14][15][16] The risk for infection has been between 1.3% and 8.7% 5,17 and exclusively for belowknee operations up to 30%. 2,4,6,18 In addition, poor preoperative skin condition and tumour ulceration 19 and patient characteristics such as diabetes, 20 smoking, 15,21 and age 3,19 are considered risk factors for surgical site infections (SSIs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestielte Lappenplastiken wie der mediale Hohlfußlappen oder der Suralislappen, Propellerlappen und bei größeren Defekten freie mikrovaskuläre Lappenplastiken, können diesem Anspruch möglicherweise gerechter werden [19]. Selbst Hautransplantate nach Wundkonditionierung mittles Vakuumversiegelung oder in Kombination mit Dermisäquivalenten auf Kosten einer längeren Behandlungsdauer mit mehreren Eingriffen, scheinen in manchen Fällen besser geeignet, einen stabilen Wundverschluss zu erzielen [20]. Trotz der immer wieder kleineren Komplikationen mit intensivierter Nachbehandlung lassen sich Defektgrößen von bis 35 cm² (ca.…”
Section: Introductionunclassified